2010
DOI: 10.1016/j.ccr.2010.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomic and Proteomic Analyses Identify Targets for Lkb1-Deficient Metastatic Lung Tumors

Abstract: Summary In mice, Lkb1 deletion and activation of KrasG12D results in lung tumors with a high penetrance of lymph node and distant metastases. We analyzed these primary and metastatic de novo lung cancers with integrated genomic and proteomic profiles and have identified gene and phosphoprotein signatures associated with Lkb1 loss and progression to invasive and metastatic lung tumors. These studies revealed that SRC is activated in Lkb1 deficient primary and metastatic lung tumors and that the combined inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
243
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(260 citation statements)
references
References 43 publications
14
243
1
Order By: Relevance
“…IPMK, an upstream kinase in the inositol polyphosphate synthesis pathway, influences LKB1 activity in a catalytic activity-dependent manner (32), suggesting that higher inositol phosphates regulate LKB1. LKB1 has been reported to suppress FAK activity-dependent migration/invasion and metastasis (16,33,34), as well as to enhance E-cadherin levels (17,19). Using MCF7 and H1299 cells with LKB1 depletion, we confirm that LKB1 down-regulates cell spreading (Fig.…”
Section: Significancesupporting
confidence: 70%
See 1 more Smart Citation
“…IPMK, an upstream kinase in the inositol polyphosphate synthesis pathway, influences LKB1 activity in a catalytic activity-dependent manner (32), suggesting that higher inositol phosphates regulate LKB1. LKB1 has been reported to suppress FAK activity-dependent migration/invasion and metastasis (16,33,34), as well as to enhance E-cadherin levels (17,19). Using MCF7 and H1299 cells with LKB1 depletion, we confirm that LKB1 down-regulates cell spreading (Fig.…”
Section: Significancesupporting
confidence: 70%
“…The tumor suppressor LKB1 has been separately reported to inhibit FAK activation (16) and to enhance E-cadherin expression (17)(18)(19). LKB1 is mutated in Peutz-Jeghers syndrome patients who tend to develop cancer at multiple sites (20).…”
mentioning
confidence: 99%
“…Studies with a mouse model of non-small cell lung cancer showed that LKB1 inactivation enhanced K-RAS-mediated metastasis and affected tumor initiation and differentiation, revealing a role for LKB1 in cancer metastasis (Ji et al, 2007;Carretero et al, 2010). However, the role of LKB1 in esophageal cancer pathogenesis remains unclear.…”
Section: Lkb1 Loss Promotes Esophageal Cancer Cell Migration and Invamentioning
confidence: 99%
“…16 Moreover, recent studies have provided strong evidences that the loss of LKB1 promotes lung carcinogenesis process, such as cell apoptosis, cycle regulation, tumor angiogenesis and metastasis. 14,17,18 The LKB1 protein as a prominent master regulator of numerous kinds of downstream kinases contributes to its tumor suppressor function. 19 It has been found that re-introduction of LKB1 in lung cancer cells can downregulate the expression of PEA3, which can suppress cell invasion by downregulation of matrix metalloproteinases (MMPs).…”
Section: Introductionmentioning
confidence: 99%